European Union view on Personal Data in Intellectual Property Rights - Dorin CIMIL; Olesea PLOTNIC (Eastern European Journal of Regional Studies)
The issue under investigation concerns whether personal data or personal information from the point of view of intellectual property constitutes as such a commodity or economic potential, which may be subject to alienation and registration as an object protected by the intellectual property system or represent a non-commercial object, without circulation in civil relations, with a special legal regime, connected to the fundamental human rights and freedoms. Recognition of personal data and other categories of information, related to the person (geolocation data, user-generated content) in terms of intellectual property rights as objects of civil rights, would allow the development of the data market, necessary for the functioning of innovative technologies on big data, cognitive calculations, the Internet of goods, and bringing these technologies into a legal and civilized field. The objective of the article is to appreciate whether personal data is subject to any intellectual property rights by the assessment of EU jurisprudence in line with national legal framework of the Republic of Moldova.